Détermination d’intérêts fédérateurs autour des enjeux de l’aire marine protégée de Bamboung (Sénégal) - Clément Sambou; Ahmadou Aly Mbaye; Ngor Ndour (VertigO)
After approximately a decade of management, it was found that actors still face difficulties in assessing the real impact of Bamboung protected area in the Saloum Delta. Based on the perceptions of local people and visitors, this study was a way to assess the environmental conditions, fisheries and ecotourism issues of Bamboung protected area. The bioecological effects are the improvement of environmental quality considered as good by local people and visitors. Related to fisheries, their effects are considered benefit by fishermen. The positive consequences of the environmental preservation are the attraction of the visitors and financial benefits. Moreover, the financial benefits from ecotourism help to ensure the financial autonomy of the MPA management. But commercial opportunities for local products, ecotourism diversification and employment are less than the expectations. It is clear that the benefits are compatible because the protection of marine ecosystems and the improvement of environmental quality have positive impact on fishing and ecotourism. Meanwhile, it was also demonstrated that the degrees of perceptions and issues of social acceptability of actions taken vary between different socio-economic actors. Indeed, fishermen are not satisfied with the establishment of the MPA. Each category, of socio-economic actors, tends to favor the choice of his activity. Also various threats and expectations have been raised by local people. This divergence of views on the issues and alternatives is the main cause of social conflict. Under these conditions, any strategy for sustainable management should go through a reorganization of the system of local management, a better distribution of financial resources and diversification of recreational activities.